Classification and detection of errors in minimally invasive surgery - Rassweiler-Seyfried, Marie-Claire; Mamoulakis, Charalambos; Kenngott, Hannes Götz; Rassweiler, Jens; Rosette, Jean; Laguna, Maria Pilar (Journal of endourology, 2011)
Purpose: To provide a comprehensive review of the classification of surgical errors as well as general measures to detect and prevent their occurrence. - - Materials and Methods: Search in PubMed, Medline, and Cochrane library with combination of the key words: Endoscopy or surgical procedures, minimally invasive, and medical error. Relevant articles were selected by three senior authors involved in minimally invasive surgery (MIS). - - Results: Error is an unintended healthcare outcome caused by a defect in the delivery of care to a patient. Surgical errors are common and account for half of all hospital adverse events (AEs). Urology is the fifth specialty in decreasing order of AE. Errors may be classified according to the place where they occur (co-face or systemic), to the outcomes (near miss, recovery, and remediation). A specific classification for errors in MIS has also been described (Cushieri), depending on the step of the surgical procedure in which they occur. Each classification serves definite purposes, and no one can be definitive over the others. No classification has been applied so far to urology. Detection through appropriate reporting is the basis for prevention. - - Conclusion: Surgical errors represent a significant proportion of all medical error. Multiple classifications exist, depending on the purposes they are intended to serve. A classification based on the place of occurrence of the errors has been adopted in the medical system; however, when referring to MIS, a finer classification is proposed.
Gesehen am 12.09.2022